2014
DOI: 10.1002/jrs.4541
|View full text |Cite
|
Sign up to set email alerts
|

In situ study of stones adorning a silver Torah shield using portable Raman spectrometers

Abstract: A silver Torah shield fitted with a set of precious stones and glass imitations crafted in Poland in the first half of the 19th century was investigated using two of the currently distributed portable and relatively low-cost Raman spectrometers in situ at the Jewish Museum in Prague. Observed Raman peaks corresponded well (+/À 3 cm À1 ) to the reference values. The hand-held instruments operated at 785-and 532-nm laser excitations showed good performance in the fast and unambiguous identification of nearly 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Osterrothova and colleagues used portable Raman spectrometers to in‐situ study stones adorning a silver Torah shield. They found that the rather chaotic mixture of stones of various colors, cuts and sizes and the total volume of imitation glass support the theory that the mounted stones were gathered from Jewish households and donated for the adornment of the shield . Schotsmans et al .…”
Section: Art and Archeologymentioning
confidence: 89%
“…Osterrothova and colleagues used portable Raman spectrometers to in‐situ study stones adorning a silver Torah shield. They found that the rather chaotic mixture of stones of various colors, cuts and sizes and the total volume of imitation glass support the theory that the mounted stones were gathered from Jewish households and donated for the adornment of the shield . Schotsmans et al .…”
Section: Art and Archeologymentioning
confidence: 89%
“…[12] A light handheld Raman spectrometer (Rigaku) equipped with a 532-nm excitation laser was used for example to detect microbial pigments under outdoor conditions for halophiles research. [5] Few studies showed until now new possibilities of direct application of portable Raman spectrometers to detect gemstones or other minerals mounted in historical artefacts: Torah shield with quartz, agates, emerald, pearls and corals [13] ; an 18th century monstrance from Prague Lesser Chapucines Treasury with numerous diamonds, garnets, amethysts, emeralds [14] and rubies; and numerous 17th and 18th century Sicilian jewels (diamonds, garnets, amethysts emeralds and rubies) collected in the frame of the Messina regional museum. [15] Beryl and its varieties Beryl Be 3 Al 2 Si 6 O 18 , a hexagonal cyclosilicate with six-membered single rings, is the most common member of the beryl group (other minerals: bazzite, indialite, stoppanite and pezzottaite).…”
Section: Introductionmentioning
confidence: 99%
“…For example, portable Raman spectroscopy has been successfully applied for the mineralogical identification of gems set on jewels preserved in museums (Reiche & Lambacher 2004;Osterrothová et al 2014;Barone et al 2015b;Barone et al 2016a), as well as in the study of loose gems (Barone et al 2016b;Bersani et al 2014). However, the value and the importance of a gem goes beyond its mineralogical composition, as origin (natural or synthetic) and geographic or geological source can add extra information in precious artifacts evaluation and characterization (to detect recent substitutions and/or reconstruct specific trading routes).…”
Section: Introductionmentioning
confidence: 99%